Sublethal effects of acaricides and Nosema ceranae infection on immune related gene expression in honeybees. (December 2016) - Garrido, Paula; Porrini, Martín; Antúnez, Karina; Branchiccela, Belén; Martínez-Noël, Giselle; Zunino, Pablo; Salerno, Graciela; Eguaras, Martín; Ieno, Elena
Abstract Nosema ceranae is an obligate intracellular parasite and the etiologic agent of Nosemosis that affects honeybees. Beside the stress caused by this pathogen, honeybee colonies are exposed to pesticides under beekeeper intervention, such as acaricides to controlVarroa mites. These compounds can accumulate at high concentrations in apicultural matrices. In this work, the effects of parasitosis/acaricide on genes involved in honeybee immunity and survival were evaluated. Nurse bees were infected withN. ceranae and/or were chronically treated with sublethal doses of coumaphos ortau -fluvalinate, the two most abundant pesticides recorded in productive hives. Our results demonstrate the following: (1) honeybee survival was not affected by any of the treatments; (2) parasite development was not altered by acaricide treatments; (3) coumaphos exposure decreased lysozyme expression; (4)N. ceranae reduced levels of vitellogenin transcripts independently of the presence of acaricides. However, combined effects among stressors on imagoes were not recorded. Sublethal doses of acaricides and their interaction with other ubiquitous parasites in colonies, extending the experimental time, are of particular interest in further research work.